A hanger shaft structure of a multilayer nanocomposite coating

CN224930141UActive Publication Date: 2026-11-03XUZHOU HUJIU MASCH MFG CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202620068446.6
Authority / Receiving Office
CN · China
Patent Type
Utility models(China)
Current Assignee / Owner
Filing Date
2026-01-20
Publication Date
2026-11-03
Estimated Expiration
2036-01-20

AI Technical Summary

Technical Problem

Existing lifting shafts are prone to wear and corrosion under harsh working conditions. Traditional coatings have insufficient adhesion and cannot simultaneously improve wear resistance, corrosion resistance and coating adhesion, resulting in frequent replacements and affecting equipment stability and safety.

Method used

A multi-layer nanocomposite coating structure is adopted, including a bonding base layer, a dense buffer layer, a tough functional layer, and a wear-resistant protective layer. AlCrN, AlCrN/TiSiN nanomultilayer and AlCrTiSiN high-entropy alloy coatings are deposited on the bearing substrate through an arc ion plating process to form a coating system with high adhesion, high hardness, and low friction.

Benefits of technology

It extends the service life of the lifting shaft, reduces the frequency of replacement, reduces the risk of vibration, improves equipment stability, reduces the probability of failure, and the thin coating thickness does not affect the assembly accuracy.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN224930141U_ABST
    Figure CN224930141U_ABST
Patent Text Reader

Abstract

The utility model is specifically related to a kind of hoisting shaft structure of multilayer nanometer composite coating, belong to shaft transmission component technical field, including hoisting shaft matrix, the connecting part is equipped at hoisting shaft matrix both ends, middle part is equipped with support part, the outer surface of support part is covered with combination bottom layer, dense buffer layer, strong tough functional layer and wear-resistant protective layer in proper order, compared with prior art, the device is combined with high bonding force, high hardness, low friction and strong corrosion resistance by multilayer coating, avoids the performance defect of traditional single coating, and in the working condition such as coal powder conveying, service life is greatly extended, replacement frequency is reduced, simultaneously, it can reduce the vibration caused by hoisting shaft abrasion, reduce chain failure risk, extend maintenance cycle, and coating thickness is thin, does not affect assembly accuracy, applicable to a variety of conveying equipment.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This utility model specifically relates to a hanging shaft structure with a multi-layer nanocomposite coating, belonging to the technical field of shaft transmission components. Background Technology

[0002] The lifting shaft is a core supporting component of material conveying equipment, widely used in industries such as cement and coal mining. Its performance directly affects the operational stability of the equipment. In actual use, the lifting shaft is subjected to harsh conditions for extended periods: on the one hand, it must withstand abrasive wear from dust, leading to surface damage; on the other hand, it is subject to erosion by corrosive media, easily resulting in rust and peeling; simultaneously, the periodic vibrations generated by equipment operation subject the lifting shaft to alternating loads, further accelerating wear and corrosion and shortening its service life.

[0003] Existing surface treatment methods for lifting shafts have significant shortcomings and are insufficient to meet the requirements of actual working conditions. Lifting shafts made of ordinary steel have low hardness and poor wear resistance, and will fail due to wear after a short period of use, requiring frequent replacement and seriously affecting production efficiency. Although a single chrome plating coating can improve hardness to some extent, its adhesion to the shaft substrate is insufficient, making it prone to peeling off under vibration, and its corrosion resistance is limited, failing to effectively resist the erosion of harsh environments.

[0004] The application of cold-sprayed alloy coatings also has drawbacks. Their density is relatively poor, and the pores within the coating can become channels for corrosive media to penetrate, leading to corrosion of the shaft substrate and affecting the overall performance of the shaft. Furthermore, cold-sprayed coatings have a high surface roughness, requiring additional processing during assembly, which not only increases costs but may also damage the coating integrity. A few improved composite coating solutions, due to insufficient consideration of the performance matching between different coatings, are prone to interfacial stress concentration during use, causing interlayer delamination and failing to simultaneously solve multiple problems such as wear and corrosion.

[0005] These issues result in short replacement cycles for the lifting shafts and frequent equipment maintenance, increasing production costs for enterprises. Furthermore, shaft wear can exacerbate equipment vibration, leading to a chain reaction of malfunctions such as bearing seizure and conveyor belt misalignment, and even posing safety hazards. Therefore, there is an urgent need for a surface-strengthening structure that can simultaneously improve the wear resistance, corrosion resistance, and coating adhesion of the lifting shafts to meet the demands of harsh working conditions and ensure the stable operation of material conveying equipment. Utility Model Content

[0006] The purpose of this invention is to address the shortcomings of existing technologies by providing a multi-layer nanocomposite coating structure for the suspension shaft. Through the synergistic effect of the multi-layer coating, the problem of easy wear and corrosion of traditional suspension shafts can be solved. This utility model achieves the above-mentioned objective through the following technical solution: a multi-layer nanocomposite coating hanging shaft structure, including a hanging shaft base, the hanging shaft base having connecting parts at both ends and a support part in the middle, the outer surface of the support part being sequentially covered with a bonding underlayer, a dense buffer layer, a tough functional layer and a wear-resistant protective layer; The bonding substrate is an AlCrN coating with a thickness of 0.2–2.0 μm; The dense buffer layer is an AlCrN / TiSiN nanomultilayer structure, consisting of alternating AlCrN and TiSiN sublayers, with a single layer thickness of 5–20 nm and a total thickness of 2.0–8.0 μm. The toughening functional layer is an AlCrTiSiN high-entropy alloy coating with a thickness of 1.0–8.0 μm; the wear-resistant protective layer is a TiSiN coating with a thickness of 0.2–2.0 μm.

[0007] Preferably, in order to improve the surface roughness of the hanger shaft base, the hanger shaft base is made of 27SiMn alloy steel, and the surface of the support part is sandblasted, with a surface roughness Ra of 1.6 to 3.2 μm.

[0008] Preferably, in order to bond the bonding underlayer to the hanger shaft base and prevent detachment, the bonding force between the bonding underlayer and the hanger shaft base is ≥50MPa.

[0009] Preferably, in order to improve the hardness of the protective middle layer, the microhardness of the toughening functional layer is 450-600 HV.

[0010] Preferably, to ensure the hardness of the outer layer of the support, the surface hardness of the wear-resistant protective layer is ≥800HV and the coefficient of friction is ≤0.45.

[0011] Preferably, in order to maintain the wear resistance of the support, the total thickness of the multilayer nanocomposite coating is 3.4 to 20.0 μm and the porosity is ≤1%.

[0012] Preferably, in order to facilitate connection with the crane, the connecting part is provided with a shaft hole, the inner wall of the shaft hole is provided with a keyway, and the surface of the connecting part is provided with an anti-rust coating.

[0013] The beneficial effects of this utility model are as follows: Compared with the prior art, this device achieves a combination of high bonding strength, high hardness, low friction and strong corrosion resistance through multi-layer coating, avoiding the performance defects of traditional single coating. In working conditions such as coal powder conveying, the service life is greatly extended, the replacement frequency is reduced, and vibration caused by wear of the suspension shaft is reduced, the risk of cascading failures is reduced, the maintenance cycle is extended, and the coating thickness is thin, which does not affect the assembly accuracy and is suitable for a variety of conveying equipment. Attached Figure Description

[0014] Figure 1 This is a schematic diagram of the overall structure of this utility model; Figure 2 This is a front view of the present invention; Figure 3 This is a schematic diagram showing the position of the support part in this utility model; Figure 4 This is a schematic diagram of the structure of the outer composite coating of the support part of this utility model; In the figure: 1. Hanging shaft base; 101. Connecting part; 102. Support part; 103. Shaft hole; 104. Keyway; 2. Bonding bottom layer; 3. Dense buffer layer; 4. Strong and tough functional layer; 5. Wear-resistant protective layer. Detailed Implementation

[0015] The technical solutions of the present utility model will be clearly and completely described below with reference to the accompanying drawings of the embodiments. Obviously, the described embodiments are only some embodiments of the present utility model, and not all embodiments. Based on the embodiments of the present utility model, all other embodiments obtained by those of ordinary skill in the art without creative effort are within the protection scope of the present utility model.

[0016] Please see Figures 1-4 As shown, a multi-layer nanocomposite coating hanger structure includes a hanger base 1, with connecting parts 101 at both ends and a support part 102 in the middle. The outer surface of the support part 102 is sequentially covered with a bonding bottom layer 2, a dense buffer layer 3, a tough functional layer 4, and a wear-resistant protective layer 5. The underlying layer 2 is an AlCrN coating with a thickness of 0.2–2.0 μm; The dense buffer layer 3 is an AlCrN / TiSiN nanomultilayer structure, consisting of alternating AlCrN sublayers and TiSiN sublayers, with a single layer thickness of 5–20 nm and a total thickness of 2.0–8.0 μm; The toughening functional layer 4 is an AlCrTiSiN high-entropy alloy coating with a thickness of 1.0–8.0 μm; the wear-resistant protective layer 5 is a TiSiN coating with a thickness of 0.2–2.0 μm.

[0017] The base of the lifting shaft 1 is made of 27SiMn alloy steel. The surface of the support part 102 is sandblasted, and the surface roughness Ra is 1.6~3.2μm. It should be noted that this material is a high-strength alloy structural steel. After quenching and tempering, the tensile strength is ≥980MPa and the impact toughness is ≥39J / cm². It can withstand the maximum load (≤50kN) and periodic vibration stress when the lifting shaft is working.

[0018] Connecting part 101: Located at both ends of the lifting shaft, used to connect with the equipment frame or main shaft, it needs to be provided with shaft hole 103 of Φ30~Φ80mm, and the inner wall of shaft hole 103 needs to be machined with keyway 104 of 8~15mm in width and 3~5mm in depth to ensure circumferential fixation with the main shaft; The surface of the connecting part 101 needs to be sprayed with an epoxy resin anti-rust coating of 80-120μm thickness to avoid corrosion in the connecting area affecting the assembly accuracy.

[0019] Support part 102: This is the core working area of ​​the lifting shaft. Its diameter is 50-100mm and its length accounts for 60%-70% of the total length of the lifting shaft. It cooperates with the inner ring of the bearing to support the main shaft. The surface of the support part 102 is sandblasted with 80-mesh corundum sand to form a uniform texture (surface roughness Ra1.6-3.2μm). Through the "mechanical interlocking" effect, the contact area with the coating is increased, and the film-substrate adhesion is improved.

[0020] The bonding strength between the bottom layer 2 and the shaft substrate 1 is ≥50MPa. It should be noted that the bottom layer 2 is made of AlCrN (aluminum chromium nitride) material, which is deposited on the surface of the support 102 by arc ion plating process. The thickness is 0.2-2.0μm (preferably 0.5μm). The coating has a columnar crystal structure (grain size 50-100nm). The bonding strength with the 27SiMn steel substrate is ≥50MPa (determined by scratch test, critical load Lc≥50N). The microhardness is 400-500HV, and the friction coefficient at room temperature is 0.5-0.6. The introduction of Al element can improve the chemical affinity between the coating and the steel substrate, and Cr element enhances corrosion resistance. The columnar crystal structure provides a uniform growth substrate for subsequent coatings and avoids early coating failure caused by defects on the substrate surface.

[0021] The microhardness of the toughening functional layer 4 is 450–600 HV. It should be noted that the toughening functional layer 4 is made of AlCrTiSiN high-entropy alloy material and is deposited by quaternary alloy target arc ion plating. The thickness is 1.0–8.0 μm (preferably 3 μm), the microhardness is 450–600 HV, the fracture toughness is 4.5–5.5 MPa・m¹ / ² (determined by indentation method), the oxidation resistance temperature is ≥600℃ (no obvious oxidation weight loss after 100 hours of heat preservation in air), the high-entropy effect (mixed entropy ΔS≥1.5R) and lattice distortion effect give the coating both high strength and high toughness, which can absorb the impact energy generated by equipment vibration (impact absorption energy ≥20J) and prevent the coating from peeling off due to fatigue load.

[0022] The wear-resistant protective layer 5 has a surface hardness ≥800HV and a friction coefficient ≤0.45. It should be noted that the wear-resistant protective layer 5 is made of TiSiN (titanium silicon nitride) material and is deposited on the surface of the tough functional layer 4 through an arc ion plating process. The thickness is 0.2~2.0μm (preferably 0.8μm). The high hardness directly resists the abrasive wear of dust particles, the low friction coefficient reduces the sliding friction loss with the inner ring of the bearing, and the smooth surface reduces the probability of dust adhesion and extends the effective service life of the grease.

[0023] The total thickness of the multilayer nanocomposite coating is 3.4 to 20.0 μm, the porosity is ≤1%, the connecting part 101 is provided with a shaft hole 103, the inner wall of the shaft hole 103 is provided with a keyway 104, and the surface of the connecting part 101 is provided with an anti-rust coating.

[0024] The present invention discloses the preparation process of the multilayer nanocomposite coating.

[0025] The multilayer nanocomposite coating was prepared in stages using a multi-target arc ion plating device (model AIP-600). The specific process is as follows: Matrix pretreatment Machining: The shaft base 1 is machined to the design dimensions by lathe, and a coating thickness allowance of 0.01 to 0.02 mm is reserved on the surface of the support part 102; Cleaning process: Use gasoline and acetone in sequence for ultrasonic cleaning (500W power, 15min time) to remove surface oil and dirt; Sandblasting: 80-mesh corundum abrasive, pressure 0.4MPa, sandblasting angle 45°, treatment time 30s, to obtain a surface roughness of Ra1.6~3.2μm; Vacuum preparation: Install the hanging shaft into the coating chamber and fix it to the rotating fixture (speed 5-10 r / min), and evacuate to 5×10⁻³ Pa.

[0026] Ion bombardment cleaning involves introducing 99.99% pure argon gas (flow rate 10 L / min), applying a -800V DC bias, and bombarding with ions for 10 min to remove the surface oxide layer and residual impurities, thereby activating the atomic activity of the substrate surface.

[0027] Combined with the bottom layer 2 sediment Target material: AlCr alloy target (Al:Cr=7:3, purity 99.9%). Process parameters: nitrogen flow rate 20L / min, working pressure 0.5Pa, bias voltage -150V, arc current 80A, deposition time 15min, to obtain a 0.5μm thick AlCrN coating.

[0028] Dense buffer layer 3 deposition Target material: AlCr target and TiSi target are used alternately (Ti:Si=9:1, purity 99.9%). Process parameters: nitrogen flow rate 20 L / min, working pressure 0.6 Pa, bias voltage -180 V, AlCr target arc current 70 A, TiSi target arc current 60 A, deposition per target 0.5 min, 40 cycles, to obtain a 4 μm thick AlCrN / TiSiN nanomultilayer structure.

[0029] Deposition of tough functional layer 4 Target material: AlCrTiSi alloy target (Al:Cr:Ti:Si=3:2:3:2, purity 99.9%). Process parameters: nitrogen flow rate 25 L / min, working pressure 0.6 Pa, bias voltage -200 V, arc current 90 A, deposition time 60 min, to obtain a 3 μm thick AlCrTiSiN high-entropy alloy coating.

[0030] 5-layer wear-resistant protective layer deposition Target material: TiSi alloy target (same as step 4); Process parameters: nitrogen flow rate 20L / min, working pressure 0.5Pa, bias voltage -180V, arc current 70A, deposition time 20min, to obtain a 0.8μm thick TiSiN coating.

[0031] After the post-treatment coating is completed, the coating is cooled to below 100°C in the furnace and then removed from the furnace. No additional heat treatment is required, thus avoiding coating oxidation or performance degradation.

[0032] Working principle This invention utilizes a four-layer coating with a gradient functional design to create a synergistic mechanism of protection, buffering, reinforcement, and bonding, as detailed below: Wear protection mechanism: Wear-resistant protective layer 5, as the outermost layer, is in direct contact with dust particles and the inner ring of the bearing. Its hardness of over 800HV can resist the indentation and cutting of hard particles. The low coefficient of friction (≤0.45) reduces the heat and wear generated by sliding friction, reducing the surface wear rate of the support 102 from the traditional 0.1 mm / week to below 0.005 mm / week. When the surface layer experiences localized wear due to long-term use, the tough functional layer 4 can continue to bear the wear-resistant function. Its hardness of 450-600 HV is still higher than that of dust particles, preventing wear from spreading rapidly to the substrate.

[0033] The dense buffer layer 3 can block the diffusion of corrosive media through the corrosion barrier mechanism: the multi-layer interface changes the diffusion path of corrosive ions from a straight line to a tortuous shape, thus reducing the diffusion rate. Meanwhile, Al and Cr elements form a passivation film on the coating surface, further inhibiting electrochemical corrosion reactions. Combined with the high adhesion between the bottom layer 2 and the substrate, it prevents corrosive media from penetrating from the coating-substrate interface, forming a synergistic anti-corrosion effect of multiple barriers. This reduces the corrosion rate of the hanging shaft in 5% NaCl solution from the traditional 0.2 mm / year to below 0.01 mm / year.

[0034] The high toughness (fracture toughness ≥ 4.5 MPa・m¹ / ²) of the stress buffering and fatigue resistance layer 4 can absorb the alternating stress generated by equipment vibration: when the bearing is subjected to a periodic load of 10–50 Hz, the plastic deformation capacity of the high-entropy alloy can alleviate stress concentration and prevent microcracks from forming in the coating; the nano-multilayer structure of the dense buffer layer 3 further disperses internal stress through interlayer slip, increasing the overall fatigue life of the coating to 10. 7 More than one cycle (traditional coatings only 10 cycles) 5 (Second time), combined with the high adhesion of the bottom layer 2, ensures that the coating deforms synchronously with the substrate, avoiding early failure caused by interface separation.

[0035] It will be apparent to those skilled in the art that this invention is not limited to the details of the exemplary embodiments described above, and that it can be implemented in other specific forms without departing from the spirit or essential characteristics of this invention. Therefore, the embodiments should be considered illustrative and non-limiting in all respects, and the scope of this invention is defined by the appended claims rather than the foregoing description. Thus, it is intended that all variations falling within the meaning and scope of equivalents of the claims be included within this invention. No reference numerals in the claims should be construed as limiting the scope of the claims.

[0036] Furthermore, it should be understood that although this specification describes embodiments, not every embodiment contains only one independent technical solution. This narrative style is merely for clarity. Those skilled in the art should consider the specification as a whole, and the technical solutions in each embodiment can also be appropriately combined to form other embodiments that can be understood by those skilled in the art.

Claims

1. A multi-layer nanocomposite coating for a hanging shaft structure, comprising a hanging shaft base (1), wherein the hanging shaft base (1) has connecting portions (101) at both ends and a supporting portion (102) in the middle, characterized in that: The outer surface of the support (102) is sequentially covered with a bonding base layer (2), a dense buffer layer (3), a tough functional layer (4), and a wear-resistant protective layer (5). The bonding substrate (2) is an AlCrN coating with a thickness of 0.2–2.0 μm; The dense buffer layer (3) is an AlCrN / TiSiN nanomultilayer structure, consisting of alternating AlCrN sublayers and TiSiN sublayers, with a single layer thickness of 5-20 nm and a total thickness of 2.0-8.0 μm; The toughening functional layer (4) is an AlCrTiSiN high-entropy alloy coating with a thickness of 1.0 to 8.0 μm; the wear-resistant protective layer (5) is a TiSiN coating with a thickness of 0.2 to 2.0 μm.

2. The hanging shaft structure with multilayer nanocomposite coating as described in claim 1, characterized in that: The shaft base (1) is made of 27SiMn alloy steel, and the surface of the support part (102) is sandblasted, with a surface roughness Ra of 1.6 to 3.2 μm.

3. The hanging shaft structure with multi-layer nanocomposite coating as described in claim 1, characterized in that: The bonding force between the bonding bottom layer (2) and the hanging shaft base (1) is ≥50MPa.

4. The hanging shaft structure with multi-layer nanocomposite coating as described in claim 3, characterized in that: The microhardness of the toughening functional layer (4) is 450-600 HV.

5. The hanging shaft structure with a multilayer nanocomposite coating as described in claim 4, characterized in that: The wear-resistant protective layer (5) has a surface hardness ≥800HV and a friction coefficient ≤0.

45.

6. The hanging shaft structure with multi-layer nanocomposite coating as described in claim 5, characterized in that: The total thickness of the multilayer nanocomposite coating is 3.4–20.0 μm, and the porosity is ≤1%.

7. The hanging shaft structure with multi-layer nanocomposite coating as described in claim 1, characterized in that: The connecting part (101) is provided with a shaft hole (103), the inner wall of the shaft hole (103) is provided with a keyway (104), and the surface of the connecting part (101) is provided with an anti-rust coating.